RANCANG BANGUN SISTEM AKUISISI DATA PROSES PENETASAN TELUR PADA INKUBATOR MENGGUNAKAN TELEMETRI - Noval Dama Riswara; Rummi Santi Rama Sirait (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2021)
This study uses a telemetry system as a long-distance communication tool, this measurement method is carried out by utilizing radio waves as a means of sending data. Measuring the temperature and humidity, which is equipped with Arduino atmega to process data, the measurement results are displayed via the LCD. The telemetry system is divided into two parts, namely the sender and the receiver. The sending unit consists of a DHT2 sensor, Ibt-2 motor driver, Ptc Ceramic Air Heater with a power of 170 watts and a voltage of 12 volts, a 12 VDC fan with a size of 12 cm x 12 cmn and a transmitter module. The receiver unit consists of a 3dr receiver module as well as data processing and storage displayed by a laptop. The purpose of this system is to reduce failures during the hatching process of chicken eggs. The Ptc Ceramic Air Heater and DC Fan components will be assembled into a control circuit using PID, with programming language using C language. Automation is carried out by measuring the temperature in the hatching room with a setpoint value of 36°C - 39°C. Temperature measurement is carried out using the DHT22 sensor, then PID tuning is carried out with the heuristic method so that in the overall test the results of the system response comparison between normal temperature and air-conditioned room temperature are obtained. This process indicates the system's performance is working well in accordance with the temperature value that can be maintained at the setpoint, where the temperature value is estimated to be able to incubate eggs.